Animal nouns in Tuvan proverbs and sayings: problems of studying and aspects of functioning - Ivanov, Eugene E.; Marphina, Zhanna V.; Shkuran, Oksana V. (The New Research of Tuva, 2022)
The article aims to trace the basic aspects of functioning and problems of studying the system of animal nouns (zoolexics) in the proverbs and sayings of the Tuvan people, with the main focus on the linguistic and linguoculturological spheres. For our sources, we have relied on the edited collections of Tuvan paremies, as well as sample paremies from the entries in dictionaries of Tuvan language.The entirety of the lexical components in proverbs and sayings is a highly specific, linguistically and linguoculturally, part of the language’s lexical corpus. Faunistic vocabulary is one of the universal thematic classes in the corpus, with animal nouns at the core of it. In this respect, the most complicated and urgent challenge is to come up with a comprehensive study of the animal noun system as it appears in Tuvan paremies, which represents both the universal features of faunistic vocabulary and the uniqueness of the animalistic conceptual sphere in the ethnic and linguistic world view of the Tuvan people.The article singles out two crucial aspects of how zoolexics functions – as a component of the lexical system and as elements of the semantic structure of Tuvan proverbs and sayings. In the linguistic sense proper, a number of problems connected with animal names have been examined, such as the place and amount of zoocomponents within the paremiac corpus, or rendering these words within the paremies when translated into Russian. There are also a number of lunguoculturological issues to be considered, including the roles zoocomponents play as representatives of key notions, as markers of paremiac imagery, and as determined by paremiac binomiality in Tuvan proverbs and sayings.
Keywords: Tuvan folklore; Tuvan language; paremiology; proverb; saying; faunistic vocabulary; zoolexeme; zoocomponent